Analysis of Stock Prices in Tiffany & Co (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
Jewelry is an adornment such as bracelet, ring or necklace made of precious metals and set with gems. One of the most famous Jewelry store is Tiffany & Co. in America. The stock of jewelry prices vary from time to time. In this paper, the stock prices of Tiffany & Co over 231 days are given. These stock price of the Tiffany & Co company are given in terms of Open, High, Low ,Closing, Volume, and Adj.CloseÂ  prices for a given time period.( almost 231 days)